GEMMP - A Google Maps Enabled Mobile Mission Planning Tool for Autonomous Underwater Vehicles - Steven Seeley; Ramprasad Balasubramanian (Institute of Advanced Engineering and Science, 2012)
Many applications for mobile robotics involve operations in remote, outdoor environments. In these environments, it can be difﬁcult to plan missions dynamically due to the lack of portability of existing mission planning software. Mobile platforms allow access to the Web from nearly anywhere while other features, like touch interfaces, simplify user interaction, and GPS integration allows developers and users to take advantage to location-based services. In this paper, we describe a prototype AUV mission planner developed on the Android platform, created to aid and enhance the capability of an existing AUV mission planner, VectorMap, developed and maintained by OceanServer Technology, by taking advantage of the capabilities of existing mobile computing technology.DOI: http://dx.doi.org/10.11591/ijra.v1i2.351